Acaricide resistance profiles of single and multi-host ticks in commercial and communal farming areas in the Eastern Cape and North-West Provinces of South Africa - Bryson, Nigel Robert (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2002.